MODERN PERSUASION: REPACKAGING AUSTEN FOR CONTEMPORARY FEMALE AUDIENCES - Kairatkyzy, Nazym (School of Sciences and Humanities, 2023)
Persuasion is the last completed novel of Jane Austen that depicts the author’s progressive vision on womanhood amid the rise of feminism in early 19th century England. The feminist director, Carrie Cracknell, revisits the novel in the 2022 Netflix adaptation to demonstrate the struggles of female characters in the society, reflecting the similarities of 19th and 21st century. The film has largely received negative criticism for deviating from the original novel in terms of representation of characters, language peculiarities and the overall message. While the adaptation, indeed, modernizes the source text and more vividly conveys the feminist agenda of the lead female characters at the expense of the novel’s features specific to the 19th century’s social and cultural spatial-temporal settings, it does so with a certain purpose. The audiences have neglected it while disapproving the adaptation for distancing from the original novel. These negative online reactions that disagree with my personal perspective on the adaptation have thus motivated me to make in-depth research on fidelity issues in Adaptation Studies, the feminist agenda in the novel and the film and identify the director’s intended message. The project will argue that by emphasizing the importance of fidelity, audiences overlook the adaptation’s purpose of addressing the problematic social stereotypes on womanhood and women’s marital and public status - which are important for female audiences in the current socio-political context. In other words, the adaptation’s urgency lies in its timely and needed message for contemporary female viewers as the director enhances the feminist voice of the main character, Anne Elliot, which is otherwise less vocal in the novel. The close reading of the novel and the script of adaptation will further help to compare the depiction of Anne Elliot’s voice and representation as well the social setting as presented in the two mediums. Besides, the negative reviews of film critics and various Twitter audience reactions to the adaptation will be used for emphasizing the bias of audiences in overestimating the value of fidelity to the text. Persuasion (2022) deviates from the source text to repackage the idea of womanhood in the society which imposes its own visions of women's public role and marital status. For instance, while the novel presents Captain Frederick Wentworth claiming that women have no right to be present on the board of a ship because they are unfit unless visiting for the ball, the film portrays him as respectful and supportive of women's professional aspirations (“It angers me the world denies you the chance of a public life”). Undoubtedly, there are similar messages in both mediums such as women's choice to marry and related social expectations since Jane Austen has already developed feminist ideas. For example, it was found that in the novel, Lady Russel’s choice not to remarry “needs no apology to the public” yet would be commonly “discontented” if she married second time; similarly, in the adaptation, when Frederick Wentworth is advertised as suitable partner for Anne Elliot, it is emphasized that “a woman without a husband is not a problem to be solved”. These instances demonstrate the director’s intention to convey the main idea of women’s liberation from the patriarchal social system and of encouraging women to make independent choices in both their marital and public life. The deviations from the source text or the lack of fidelity to the text are thus necessary for conveying this idea to modern female audiences. Moreover, adaptations need to be informed of the current cultural and socio-political context to present a film that is relevant and to allow the adaptation to be an independent artwork. Thus, more similar findings based on the close reading of primary sources and survey of secondary sources would be presented to argue for the importance of Netflix’s take on revisiting Austen for delivering a message to contemporary female audiences. In relation to previous study on Jane Austen’s novels’ adaptations, this research is the first academic research on the newest Netflix adaptation of Austen’s Persuasion. Moreover, it puts into dialogue the adaptation, source text and two types of audience reviews - from film critics and social media users - which stands out from previous research that included analysis of the adaptation and film critics only. Thus, while the theme of this research has been in exploration before through Feminist Film Studies and Adaptation Studies, my project makes a comprehensive analysis of many sources and theories.
Keywords: Type of access: Open Access; Film adaptations; Jane Austen; Persuasion; fidelity; Audience Studies; female representation on screen; Fan Studies